La génesis del Estado republicano en Colombia: Elementos para una historia social de la administración pública - Roth Deubel, André-noël (Cuadernos de Historia del Derecho, 2007)
The birth of the republican State in Colombia is marked by a process of modernization of the political and administrative institutions that is chronologically coincident with the process of Independence and constitution of the Colombian Nation. The article undertakes the study of the process of modernization of the State from the analysis of the modernization attempts frome part of the public administration, since its centralization and expansion constitute the key elements of the new state, its institutions and its legitimation. It is considered that the process of modernization in Colombia was truncated, at least partially, due to the failure of this modernization process. Through the case of the public administration of the Cauca Department at the time of the Great Colombia (1821-1830), three aspects are analyzed to give reason of this hypothesis: the absence of a competitive staff, the lack of resources and the little and very limited diffusion and appropriation of the ideas of the Illustration.